Political shocks and inflation expectations: Evidence from the 2022 Russian Invasion of Ukraine - Lena Dräger; Klaus Gründler; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
How do global political shocks influence individuals' expectations about economic outcomes? We run a unique survey on inflation expectations among 145 tenured economics professors in Germany and exploit the 2022 Russian invasion in Ukraine as a natural experiment to identify the effect of a global political shock on expectations about national inflation rates. We find that the Russian invasion increased short-run inflation expectations for 2022 by 0.75 percentage points. Treatment effects are smaller regarding mid-term expectations for 2023 (0.47 percentage points) and are close to zero for longer periods. Text analysis of open questions shows that experts increase their inflation expectations because they expect supplyside effects to become increasingly important after the invasion. Moreover, experts in the treatment group are less likely to favor an immediate reaction of monetary policy to the increased inflation, which gives further evidence of the shock being interpreted primarily as a supply-side shock.
Keywords: E31; E71; D74; D84; 330; inflation expectations; belief formation; natural experiment; 2022 Russian invasion of Ukraine; survey; economic experts